(3OaY GdETcGd Ydi eG aj bhdg JYGdi (B{ (3hdh Yde Gddg ajge NjQG dCSeYge hdh CSeYge dJhdhG (B}s - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO defRd GdcJGH hGdUdGI degOj GdUhGH agPg cdeGJ eJYdbI Ydi bhdg aj ShQI GdCfYGe (B{ (3hdh Yde Gddg ajge NjQG dCSeYge hdh CSeYge dJhdhG (B} (3OGaYI deG jJhge ef GdETcGd ef Gfg Tcd Chd (B( (3cPG (B) (3eY Cf GdfJjLI eMGd heJVefI dOaY eG jJhge ef GdJfGbV s
(3BNQgG (B:s
(3hHeG bQQfG CjVG YQaJ OaY Jhge GdJfGbV Hjf eG ajge ef GdebOeI GdKGfjI ef Cfge eG JhdhG hGfJaGA GdeJhdj ef GdChdi ef Cfg dG NjQ ajge aj ehGVY eJYOOI gPG eY JdGWe CehGL GdYhGFb hYOe JaQZ GdCPgGf Yf GdYGFb hGdHMKs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds